(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Taxonomical, biomorphological, ecological, coenotical and geographical structure of the flora of plant communities with paleoendemic Chamaecytisus graniticus Rothm. (Fabaceae Lindl.) are studied with its autphytosozological analysis.